Adaptive plasticity in response to light and nutrient availability in the clonal plant Duchesnea indica. (2nd October 2021) - Wang, Mo-Zhu; Li, Hong-Li; Liu, Chun-Xiang; Dong, Bi-Cheng; Yu, Fei-Hai
Abstract: Phenotypic plasticity enables plants to buffer against environmental stresses and match their phenotypes to local conditions. However, consistent conclusive evidence for adaptive plasticity has only been obtained for a few traits. More studies on a wider variety of plant functional traits and environmental factors are still needed to further understand the adaptive significance of plasticity. We grew 21 genotypes of the stoloniferous clonal plant Duchesnea indica under different light and nutrient conditions, and used selection gradient analyses to test the adaptive value (benefits) of morphological and physiological plasticity responding to variation in light and nutrient availability. Plants grown in shade exhibited lower values for fitness measures (fruit number, ramet number and biomass), shortened thinner internode length and decreased adult leaf chlorophyll content, but higher petiole length, specific leaf area and old leaf chlorophyll content, than plants grown without shade. Plants grown in the low nutrient condition had shorter petiole length, thicker and smaller leaf area, lower chlorophyll content, but higher fruit number and root:shoot ratio than plants grown under the high nutrient condition. Selection gradient analyses revealed that plasticity of petiole length and old leaf chlorophyll content in response to light variation was adaptive, and plasticity of old and adult leaf chlorophyll content in response to nutrient variation was adaptive. Therefore, the adaptive value of plasticity in different traits depends on the specific ecological context. Our findings contribute to understanding the adaptive significance of phenotypic plasticity of clonal plants in response to environmental variation.